Stress Factors and Their Association with Mental Health Problems Among Public Health Students in Makassar: A Cross-Sectional Path Analysis Study - Shanti Riskiyani; Ani Asram; Rizky Chaeraty Syam; Masriadi; A. Febriani Tenri Sa'nna (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Student mental health remains a major concern in higher education, particularly among final-year students who face increasing academic and personal pressures. This study aimed to examine the role of stress as a mediator between personal and family factors and mental health among public health students in Makassar. Methods: A cross-sectional study was conducted involving 279 final-year students. Data were analyzed using path analysis to evaluate direct and indirect relationships among variables. Results: The findings indicate that personal factors significantly increased stress across all educational levels, while family factors were significant primarily among undergraduate students. Stress demonstrated a consistent and increasingly strong negative effect on mental health from undergraduate to doctoral levels (? = -0.532 to -0.709). Personal factors influenced mental health mainly through stress mediation, whereas the role of family support diminished at higher academic levels. These results highlight a developmental shift in mental health determinants from external support toward internal coping demands as academic level increases. Conclusion: The study underscores the importance of level-specific mental health strategies focusing on family support for undergraduates and stress management interventions for postgraduate students.